Free convective heat transfer coefficient for high powered and tilted QFN64 electronic device. (November 2016) - Baïri, A.
Abstract: Heat exchanges occurring between the electronic assemblies and their environment are an essential data in order to control their temperature, enhance their performance and improve their reliability. In this survey, the average natural convective heat transfer coefficient is determined for an assembly constituted by a Quad Flat Non-lead QFN64 generating a high power ranging from 0.1 to 1.0 W during operation. It is welded on a PCB which may be inclined with respect to the horizontal plane by an angle varying between 0° and 90°. The calculations done by means of the finite volume method show how the free convective heat transfer on every part of this electronic assembly is influenced by these physical parameters. The correlations proposed in this work allow calculating the convective heat transfer coefficient in any area of the considered assembly according to the generated power and the tilt inclination. These original and unpublished tools allow increasing reliability and better thermal control of this conventional device widely used in electronics for many engineering applications. Highlights: The natural convective heat transfer coefficient is quantified for the QFN64 device. The proposed correlations provide a better modeling of the high powered QFN64 device. The study optimize the thermal design and temperature control of the active QFN64. Effects of electronic assembly's inclination and power on free convection are treated.